Iron regulates the expression of ferroportin 1 in the cultured hFOB 1.19 osteoblast cell line - ZHAO, GUO-YANG (D.A. Spandidos, 2014)
Iron metabolism is tightly regulated in osteoblasts, and ferroportin 1 (FPN1) is the only identified iron exporter in mammals to date. In the present study, the regulation of FNP1 in human osteoblasts was investigated following various iron treatments. The human osteoblast cell line hFOB 1.19 was treated with ferric ammonium citrate (FAC) or desferrioxamine (DFO) of various concentrations. The intracellular iron ion levels were measured using a confocal laser scanning microscope. In addition, the mRNA and protein expression levels of FPN1 were detected by quantitative polymerase chain reaction, western blot analysis and immunofluorescence. The results demonstrated that increasing iron concentrations via FAC treatment increased the expression of FPN1. By contrast, decreasing the iron concentration by DFO treatment decreased FNP1 expression levels. In addition to demonstrating that the FNP1 expression changed according to the iron concentration, the observations indicated that changes in FPN1 expression may contribute to the maintenance of the intracellular iron balance in osteoblasts.